Identification of crucial salivary proteins/genes and pathways involved in pathogenesis of temporomandibular disorders - Talian Ivan; Laputková Galina; Schwartzová Vladimíra (Open Chemistry, 2022)
Temporomandibular disorder (TMD) is a collective term for a group of conditions that lead to impairment of the function of the temporomandibular joint. The proteins/genes and signaling pathways associated with TMD are still poorly understood. The aim of this study was to identify key differentially expressed salivary proteins/genes (DEGs) associated with TMD progression using LC-MS/MS coupled with a bioinformatics approach. The protein–protein interaction network was obtained from the STRING database and the hub genes were identified using Cytoscape including cytoHubba and MCODE plug-ins. In addition, enrichment of gene ontology functions and the Reactome signaling pathway was performed. A total of 140 proteins/genes were differentially expressed. From cluster analysis, a set of 20 hub genes were significantly modulated: ALB, APOA1, B2M, C3, CAT, CLU, CTSD, ENO1, GSN, HBB, HP, HSPA8, LTF, LYZ, MMP9, S100A9, SERPINA1, TF, TPI1, and TXN. Two enriched signaling pathways, glycolysis and gluconeogenesis, and tryptophan signaling pathway involving the hub genes CAT, ENO1, and TPI1 have been identified. The rest of the hub genes were mainly enriched in the innate immune system and antimicrobial peptides signaling pathways. In summary, hub DEGs and the signaling pathways identified here have elucidated the molecular mechanisms of TMD pathogenesis.